2006
DOI: 10.1086/508219
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Profile and Clinical Associations of Human Bocavirus and Other Human Parvoviruses

Abstract: In the present study, HBoV was a frequently detected, potential respiratory pathogen, with a prevalence and an epidemiological profile comparable to those of RSV. Identification of HBoV infections may be clinically important in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
218
3
28

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(273 citation statements)
references
References 16 publications
24
218
3
28
Order By: Relevance
“…However, it is interesting to note that in all countries seroprevalence appeared to stay constant or decrease in very young children (less than 4 years of age), whereas one would expect it to increase following the loss of maternal antibodies in the first year of life. The reasons for this are unclear, but could include a lack of assay specificity for this age group exposed to many other viral agents including possibly the recently discovered human bocavirus belonging to the family Parvoviridae [14] .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is interesting to note that in all countries seroprevalence appeared to stay constant or decrease in very young children (less than 4 years of age), whereas one would expect it to increase following the loss of maternal antibodies in the first year of life. The reasons for this are unclear, but could include a lack of assay specificity for this age group exposed to many other viral agents including possibly the recently discovered human bocavirus belonging to the family Parvoviridae [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, hMPV is a new member of the Paramyxoviridae family, Pneumovirus subfamily (Chan et al 2007), showing a incidence rate between 3.9-9% in young children with ARTI (Manoha et al 2007). Molecular techniques are powerful tools to search for respiratory pathogens that may be present in clinical samples, especially from patients suffering from respiratory infections (Manning et al 2006). We have studied the occurrence of hBoV and hMPV in the Porto Alegre (PA) metropolitan area, one of the southernmost cities of Brazil, evaluating children suspected to have a lower respiratory tract infection during a 13-month period.…”
mentioning
confidence: 99%
“…Some studies showed that HBoV is responsible for severe infections of the lower respiratory tract in small children but less data are available on the role of HBoV in gastroenteritis [7]. The frequency of HBoV differs between countries (Canada 1.5%, Sweden 3.1%, Australia 5.6%, and Japan 5.7%, Germany 10.3% and Korea 11.3%) [8][9][10][11][12][13][14] but its prevalence in Iran is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…AGE is a common cause for hospital admission in Iranian children [11][12][13][14][15][16]. Rota virus antigen obtained from stool of AGE cases between 15-47% of hospitalized children with AGE, just in 12% of controls group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation